2010
DOI: 10.1186/1748-717x-5-16
|View full text |Cite
|
Sign up to set email alerts
|

Cytokines levels, Severity of acute mucositis and the need of PEG tube installation during chemo-radiation for head and neck cancer - a prospective pilot study

Abstract: BackgroundThe purpose of this pilot study was to detect a correlation between serum cytokine levels and severity of mucositis, necessitating installation of a percutaneous endoscopic gastrostomy tube (PEG) in head and neck (H&N) cancer patients receiving combined chemo-radiation therapy.Patients and MethodsFifteen patients with H&N epithelial cancer were recruited to this study. All patients received radiotherapy to the H&N region, with doses ranging from 50-70 Gy. Chemotherapy with cisplatin, carboplatin, 5-f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
61
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 24 publications
(39 reference statements)
8
61
1
1
Order By: Relevance
“…Previous studies have shown IL6 upregulation to be one of the earliest detected responses to radiation-induced tissue injury (33)(34)(35). Our above findings suggested that IL6 is also linked to the later expression of senescence-associated markers in the irradiated salivary glands.…”
Section: Il6 Signaling Enhances Radiation-induced Senescence In the Ssupporting
confidence: 58%
“…Previous studies have shown IL6 upregulation to be one of the earliest detected responses to radiation-induced tissue injury (33)(34)(35). Our above findings suggested that IL6 is also linked to the later expression of senescence-associated markers in the irradiated salivary glands.…”
Section: Il6 Signaling Enhances Radiation-induced Senescence In the Ssupporting
confidence: 58%
“…In addition to our previous findings with 58 patients [4] and current findings in this study, Hart et al also reported that low IL-8 was correlated with increased risk of RILT in NSCLC [20]. Meirovitz et al found that low IL-8 was associated with the need for percutaneous endoscopic gastrostomy (PEG) tube installation due to mucositis during RT of head and neck squamous cell cancers [21]. Though there are few reports on the role of IL-8 in predicting radiation induced toxicity, these findings were consistent with our findings in that the lower the baseline IL-8 level, the higher the toxicity.…”
Section: Discussionsupporting
confidence: 78%
“…IL-8 is interesting, as it has chemotactic activity for leukocytes and induces collagen synthesis and cell proliferation [19] in animal studies but it has been consistently found to have anti-inflammatory effect in humans [20] [21]. In addition to our previous findings with 58 patients [4] and current findings in this study, Hart et al also reported that low IL-8 was correlated with increased risk of RILT in NSCLC [20].…”
Section: Discussionsupporting
confidence: 71%
“…Elevations in cancer-related and treatment-induced circulating inflammatory cytokines may be partially responsible for the development of clusters of symptoms (e.g., pain, fatigue, distress, and disturbed sleep; the symptom equivalent of tumor burden that is often referred to as ‘symptom burden’) during RT. For example, a positive correlation was found between IL-6 serum levels and severity of mucositis and dysphagia in head and neck cancer patients receiving combined chemoradiation therapy [13]. Also, pro-inflammatory cytokines (IL-6, -10 and TNFR1) are over-expressed in non-small cell lung cancer patients undergoing chemoradiation therapy [188].…”
Section: Targeting Pro-inflammatory Response To Reduce the Side-efmentioning
confidence: 99%